QATH’IY AND ZHANNIY PRINCIPLES IN ISLAMIC INVESTMENT: IMPLICATIONS FOR RISK MANAGEMENT - Raudatul Janah, Nisa; Hasan , Mustofa (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
Investment and financing in Islamic banking are fundamental aspects in the development of the Islamic economy. The principles of Qath'iy and Zhanniy taken from the Qur'an are important guidelines in the management of Islamic financial transactions. This study aims to analyze the application of these two principles in Islamic investment and financing and their implications for risk management. Using the normative juridical method, this research examines various Islamic financial products such as mudharabah, musyarakah, and murabahah, and identifies how these principles help create stability and transparency in Islamic banking, while minimizing the risks that can arise due to uncertainty and speculation.